2020
DOI: 10.4252/wjsc.v12.i11.1237
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelets and breast cancer stem cells in metastasis

Abstract: The high mortality rate of breast cancer is mainly caused by the metastatic ability of cancer cells, resistance to chemotherapy and radiotherapy, and tumor regression capacity. In recent years, it has been shown that the presence of breast cancer stem cells is closely associated with the migration and metastatic ability of cancer cells, as well as with their resistance to chemotherapy and radiotherapy. The tumor microenvironment is one of the main molecular factors involved in cancer and metastatic processes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 144 publications
(123 reference statements)
0
22
0
Order By: Relevance
“…Platelet α-granules released after platelet activation carry a large amount of growth factors, such as PDGF, VEGF and TGF-β. In the TME, these growth factors are conducive to tumor proliferation, angiogenesis and invasiveness, thereby promoting tumor progression ( 112 ). At the same time, these factors cooperate with heparanase and matrix metalloproteinases (MMPs) in the TME to further promote tumor-related thrombosis ( 113 ).…”
Section: Nets and Cancer-related Thrombosismentioning
confidence: 99%
“…Platelet α-granules released after platelet activation carry a large amount of growth factors, such as PDGF, VEGF and TGF-β. In the TME, these growth factors are conducive to tumor proliferation, angiogenesis and invasiveness, thereby promoting tumor progression ( 112 ). At the same time, these factors cooperate with heparanase and matrix metalloproteinases (MMPs) in the TME to further promote tumor-related thrombosis ( 113 ).…”
Section: Nets and Cancer-related Thrombosismentioning
confidence: 99%
“…(4) Metastatic cells become ready for intravasation into the microvessels generated by angiogenesis in the TME [14], developing the ability to attract and conglomerate platelets around them. Platelets provide metastatic cells with the protection they need to travel without being destroyed by the shear force generated by circulating blood or natural killer (NK) cells [15]. These so-called circulating tumor cells (CTC) can extravasate at a site distant from their point of origin, forming a new metastatic focus with the help of platelets [16].…”
Section: Overviewmentioning
confidence: 99%
“…Now they are in the focus of several research groups worldwide due to their enormous potential to change our paradigmatic understanding of the development of several diseases. Platelets are currently an important focus of research due to their role in developing cancer, angiogenesis, and metastasis [15]. They have various membrane-bound organelles, including mitochondria, alpha granules, dense granules, and lysosomes, in addition to a complex membranous system, known as the open canalicular system (OCS), which allows for the connection of cytosol (as an external medium) and the dense tubular system (DTS), which stores essential metabolic enzymes [18].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Each genotypic and phenotypic change gives way to alterations in the tumor microenvironment and tumor progression [6]. It has been observed that all types of cancer share genetic alterations, especially in the signaling pathways that control cell progression, apoptosis, and cell growth [7,8].…”
Section: Introductionmentioning
confidence: 99%